Pengaruh Return on Assets (ROA) dan Kebijakan Dividen terhadap Nilai Perusahaan pada Perusahaan Sektor Industri yang Terdaftar DEI - Mely Maryanti (YASIN, 2026)
Firm value serves as an indicator of the market’s assessment of a company’s performance and future prospects, while also shaping investors’ perceptions of management’s ability to manage available resources. One of the key factors determining firm value is profitability, which reflects a company’s ability to generate profit within a given period. This study aimed to analyze the effect of Return on Assets (ROA) and Dividend Payout Ratio (DPR) on firm value in consumer goods manufacturing companies in the food and beverage sub-sector listed in the Daftar Efek Syariah (DES) for the 2018–2023 period. The research used secondary data with a sample of 6 companies out of 901 selected through a purposive sampling technique. A descriptive quantitative approach was employed, with data analysis techniques comprising descriptive statistics, panel data regression analysis, selection of the appropriate panel data regression estimation model, classical assumption tests, hypothesis testing, and the coefficient of determination (R²). The results showed that, partially, ROA did not have a significant effect on firm value, whereas DPR had a significant effect on firm value. Simultaneously, ROA and DPR had a significant effect on firm value. These findings underscore that, in the context of consumer goods manufacturing companies in the food and beverage sub-sector listed in the DES, dividend policy plays a more prominent role in influencing firm value than accounting-based profitability indicators, and thus may serve as an important consideration for management and investors in financial and investment decision-making.